Optimization of Ethanol Extraction Process of Solanum nigrum Linn. and Structural Confirmation of its Compounds - Guo, Shan-Bin; Tian, Yue; Jian, Ling-Yan (Asian Journal of Chemistry, 2014)
This work reported the optimization of the ethanolic extraction process of Solanum nigrum Linn. and isolation, purification and identification of alkaloid constituents in Solanum nigrum Linn.. Orthogonal design was used to study the process optimization conditions, repeated silica gel column chromatography, preparative TLC, ODS column chromatography, Sephadex LH-20 column chromatography and preparative HPLC were used to isolate the compounds. It can be seen from the results of orthogonal experiment and variance analysis that, the optimal extraction process of Solanum nigrum Linn. with solasonine yield as investigation index is A3D3B3C3, i.e. addition of a 10-fold amount of 90 % ethanol, three times of extraction and extraction duration of 3 h each; four compounds, namely solamargine, solasonine, uttroside A and uttroside B, were isolated by subjecting the alkaloid fraction of Solanum nigrum Linn. to repeated silica gel column chromatography, preparative TLC, ODS column chromatography, Sephadex LH-20 column chromatography and preparative HPLC. 90 % ethanol can be used in the extraction of Solanum alkaloids, Solanum nigrum Linn. contains constituents such as solamargine, solasonine, uttroside A and uttroside B.